Analysis of Social Interaction Skills of Children With Special Needs With Intellectual Disabilities in SLBN School Bekasi Regency - Srinawati Dewi; Nurlaila Tussadiah; Oktavia Duwi Salsadila; Fitriyani Fitriyani (Pusdikra-Publishing.com, 2024)
This article discusses the ability of children with intellectual disabilitiesto improve social interaction and learning skills for children with intellectual disabilities. Intellectual impairment is a special condition that affects cognitive development in children. This article uses qualitative methods, data collection in this study is carried out by observation, interviews with teachers and documentation and assisted by scientific papers, books, references, and others whose purpose is to analyze the social interaction ability of children with special needs with intellectual disabilities in the school environment. The results in this study show that children with intellectual disabilities face challenges in developing their social interaction skills in the school environment. Factors such as difficulty interacting socially with their peers, lack of self-confidence in children, and always withdrawing from their peers. However, the teacher's efforts or strategies in dealing with children with intellectual disabilities are an inclusive approach in classroom management and teachers provide understanding to their friends to approach and join children so that they can play together and get treatment from the teacher.